Automatic Fish Feeder - Jumat, Mieor Ahmad Safwan Meor Abd (Universiti Sains Malaysia, 2017)
Improper fish feeding system leads to feed waste as well as contributing to environmental impact such as water pollution. The development of an automatic fish feeder is to overcome this issue. The main purpose of this project is to help the aquarist fish who have the hectic which unable to maintain the regular care of feeding. The automatic fish feeder is controlled by a real time clock (RTC) and it is capable of feeding the fish in accordance with a pre-determined time schedule without the presence of an operator. The feeder can select any of the desired amount of feeding and conveniently choose the schedule for feeding. Once the schedule has been set, the servo motor will rotate and open the container to feed the fish accordingly. The other part in this project is the warning system. It is to alert the user to fill the pellet into the container. Due of this circumstance, it become very helpful to the aquarist fish.